Successful Primary Coronary Intervention and Invasive Blood Pressure Monitoring During Lund University Cardiopulmonary Assist System (LUCAS) Mechanical Chest Compression: Case Report - Tabatabai, Sadeq; Khalifeh, Ali; Alhashmi, Jasem Mohammed (Dubai Medical Journal, 2025)
Introduction: Acute ST-segment elevation myocardial infarction demands urgent intervention to restore coronary blood flow, with primary percutaneous coronary intervention (PCI) as the preferred treatment. However, sudden cardiac arrest remains a significant complication, occurring in approximately 1.3% of PCI patients. In such critical situations, delivering high-quality and uninterrupted cardiopulmonary resuscitation (CPR) is a priority. CPR in acute myocardial infarction presents challenges and opportunities when combined with primary PCI. The key to favorable outcomes is immediate resuscitation efforts and timely revascularization of the occluded artery. However, conflict arises between these actions. Case Report: We report a case of a 54-year-old male patient who suffered an acute myocardial infarction and underwent successful primary PCI with invasive blood pressure monitoring while being in cardiac arrest, as well continuous CPR with the use of the Lund University Cardiopulmonary Assist System (LUCAS), an automated chest compression device. We documented an invasive blood pressure measurement up to 161/69 mmHg during CPR. Discussion: Manual CPR in catheterization laboratories is challenging due to space limitations and radiation, especially in cases of refractory prolonged cardiac arrest. Mechanical chest compressors are a potential alternative but their efficacy and practicality are still being explored. Simply because arterial cannulation limits blood pressure measurement, there is little thorough evidence on hemodynamic outcomes with mechanical chest compressions. Conclusion: The evolution of mechanical CPR in catheterization laboratories necessitates ongoing research and clinical guidelines to optimize its application and ensure optimal patient care.